Induced Mutagenesis for Realizing Temperature Sensitive Genic Male Sterility in Rice (Oryza sativa L.) - Anithadevi, K. S.; Raveendran, T. S. (International Journal of Bio-resource and Stress Management, 2010)
An investigation was carried out to generate genetic variability in two rice varieties viz., ADT 39 and CR 1009 by exposing them to gamma rays at 50, 100, 150, 200, 250 and 300Gy. The main focus of this study is to identify environmentally controlled genetic male sterile mutants which upon further investigation could help in hybrid breeding programme. The male sterile plants were identified in M2 generation under high temperature condition (Coimbatore) and the reverted lines (with more than 60% spikelet fertility) in the low temperature region (Gudalur) were planted again in the high temperature condition to confirm their Temperature sensitive Genic male sterilirty (TGMS) nature. Seven plants (comprising five plants from ADT 39 and two plants from CR 1009) isolated from M3 generation recorded to have 100 % pollen and spikelet sterility.